Applying a Sociological Approach in Non-formal Education - Zulhadrizal, Zulhadrizal; Syur'aini, Syur'aini; Sunarti, Vevi (Universitas Negeri Padang, 2024)
This writing aims to discuss the application of a sociological approach in non-formal education. Sociology is a science that studies human relations with humans. The sociological approach in non-formal education is to look at relationships and apply sociological principles in implementing learning in non-formal education. The sociological approach that can be applied in non-formal education can be seen from the relationship between the non-formal education system and the existing system in society, non-formal education and the community, humans and non-formal education, and the influence of non-formal education on student behavior.Keywords: application, sociological approach, non-formal education, society, students